2018
DOI: 10.1002/pits.22123
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural school psychology training: An examination of students’ self‐reported course outcomes

Abstract: This mixed methods study examined the outcomes of a multicultural course on school psychology students' feelings of empathy and sensitivity toward members of different racial and ethnic groups. It also investigated students' perceptions of how the course would influence their future practice as school psychologists. Ethnic identity awareness was explored across ethnic groups and in relation to students' feelings of empathy and sensitivity toward members of different racial and ethnic groups. Results showed dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, the assessment effectiveness has been criticized because of the numerous ways in which competencies are defined and taught and the ways in which outcomes are measured (Gorski, 2009; Paul-Binyamin & Reingold, 2014). Also, more information is needed on the direct pathways, coursework, and delivery method in which individuals develop said competencies (Vega, Tabbah, & Monserrate, 2018). Although measures such as the Multicultural School Psychology Counseling Competency, Cross-Cultural Counseling Inventory (Reyna et al, 2017), and self-reported measures of change (Tomlinson-Clarke, 2000) are arguably different, their results are discussed in the same way when defining, assessing, and reporting aims of cultural competencies and multicultural coursework.…”
Section: Diversity Courseworkmentioning
confidence: 99%
“…However, the assessment effectiveness has been criticized because of the numerous ways in which competencies are defined and taught and the ways in which outcomes are measured (Gorski, 2009; Paul-Binyamin & Reingold, 2014). Also, more information is needed on the direct pathways, coursework, and delivery method in which individuals develop said competencies (Vega, Tabbah, & Monserrate, 2018). Although measures such as the Multicultural School Psychology Counseling Competency, Cross-Cultural Counseling Inventory (Reyna et al, 2017), and self-reported measures of change (Tomlinson-Clarke, 2000) are arguably different, their results are discussed in the same way when defining, assessing, and reporting aims of cultural competencies and multicultural coursework.…”
Section: Diversity Courseworkmentioning
confidence: 99%
“…The standalone coursework builds trainees’ knowledge of multicultural terminology, specific cultural groups, and multicultural interventions (Fouad, 2006; Mallott, 2010). It can also help trainees increase their awareness of and sensitivity to cultural issues (Patterson, Papa, Reveles, & Domenech Rodríguez, 2018; Vega, Tabbah, & Monserrate, 2018). The integration of multicultural content in core school psychology courses emphasizes to trainees that multiculturalism is central to all school psychology practice.…”
Section: A Snapshot Of the State Of Multicultural Training In School mentioning
confidence: 99%
“…Moreover, representations have the power to facilitate a sense of connection to others, both nationally and globally (Edelman, 2015). With exposure to new representations comes new knowledge, which students can integrate with their understanding of the self and society, enhancing their awareness of and actions in the multicultural environments they inhabit (Vega et al, 2018). For this process among representations , connections , and integration to occur, research has recommended that MPs/DS be included in psychology coursework (Alvarez et al, 2019).…”
Section: Leveraging the Power Of Representation: The Interview With A...mentioning
confidence: 99%